2016
DOI: 10.1186/s12917-016-0907-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide derived from the digestive tract triggers an inflammatory response in the uterus of mid-lactating dairy cows during SARA

Abstract: BackgroundThe aims of the current study were to evaluate the inflammatory response in cow uterus and to explore the molecular mechanism triggered by high concentrate-induced subacute ruminal acidosis (SARA) in mid-lactating dairy cows. Twelve mid-lactating Holstein cows with an average weight of 455 kg were allocated into two groups subjected to two diets for 18-weeks either a low-concentrate (LC) group containing 4:6 (NDF: NFC) and a high-concentrate (HC) group containing 6:4 (non-forage carbohydrates, NFC): … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 48 publications
(67 reference statements)
1
31
0
Order By: Relevance
“…These milk composition reduced because the free circulating LPS may decrease the activity of key enzymes in milk component syntheses, such as acetyl-CoA carboxylase, fatty acid synthase, and lipoprotein lipase [ 15 ]. Consistent with previous SARA studies we observed increased levels of proinflammatory cytokines in goats fed HG alone [ 36 ] and conversely these proinflammatory cytokines were prominently decreased in goat fed HG with NaB. These further confirmed the presence of SARA in a group of goats fed high grain diets.…”
Section: Discussionsupporting
confidence: 92%
“…These milk composition reduced because the free circulating LPS may decrease the activity of key enzymes in milk component syntheses, such as acetyl-CoA carboxylase, fatty acid synthase, and lipoprotein lipase [ 15 ]. Consistent with previous SARA studies we observed increased levels of proinflammatory cytokines in goats fed HG alone [ 36 ] and conversely these proinflammatory cytokines were prominently decreased in goat fed HG with NaB. These further confirmed the presence of SARA in a group of goats fed high grain diets.…”
Section: Discussionsupporting
confidence: 92%
“…(Figure 1; Tomlinson and Blikslager, 2004), and these cytokines are expected to initiate the synthesis of serum amyloid A (SAA) and haptoglobin (Hp) in the liver (Figure 1). Some studies have indeed shown that grain-induced SARA increased the concentrations of TNF-α, IL-1β and IL-6 in peripheral blood plasma of cows (Bilal et al, 2016;Guo et al, 2017) and goats (Chang et al, 2015). However, Li et al (2016), observed that, despite increases in SAA, Hp and LBP, grain-induced SARA reduced the blood plasma concentration of IL-6, and did not affect that of TNF-α.…”
Section: Gastrointestinal Health and Inflammationmentioning
confidence: 99%
“…Hence, a malfunctioning of the liver, such as that often seen in early lactation, could aggravate the LPS-related symptoms of SARA. The effects of SARA challenges on the concentration of LPS in blood plasma, therefore, vary greatly among studies, as in the studies of Supplementary Material S2, LPS was only detected in blood plasma by Chang et al (2015), Bilal et al (2016) and Li et al (2016), which shows that LPS can translocate out of the digestive tract. The discrepancies among studies may be due to differences in the duration and severity of the SARA challenge, and thresholds below which LPS does not translocate.…”
Section: Gastrointestinal Health and Inflammationmentioning
confidence: 99%
“…Under such circumstances, endotoxin (lipopolysaccharide, LPS), a cell wall component of Gram-negative bacteria, is released in an increasing amount in the rumen [1,2,3,5]. Several studies showed when dairy cows were fed high-concentrate diets, both ruminal and circulating LPS increased [6,7,8,9,10,11]. Studies also demonstrated feeding dairy cows high-concentrate diets resulted in increased LPS concentrations in the mammary artery plasma as compared with cows fed with low-concentrate diets [12,13].…”
Section: Introductionmentioning
confidence: 99%